What Hope for Open Knowledge? Productive (Armed) vs. Connective (Tribal) Knowledge and Staged Conflict - Hartley John (Cultural Science)
The paper distinguishes between two kinds of knowledge, productive or armed knowledge and connective or tribal knowledge, which it traces back to pre-modern antagonisms. It argues that open knowledge depends on a new ‘agonistic’ synthesis of these types. The aim is partly to show that culture is primary in determining what knowledge means and who gets to share it; and partly to compare formal knowledge institutions (especially universities) with informal knowledge systems (language and social media). Can knowledge ever be open if it is either armed or wild? If so, then how should we model openness? I suggest that situating knowledge in language, performance and play, rather than property and productivity, offers a way forward.